(untitled) (London, 1975)
Content: Born at the height of the Heian period, the pseudonymous Lady Sarashina reveals much about the Japanese literary tradition in this haunting self-portrait. Born in 1008, Lady Sarashina was a lady-in-waiting of Heian-period Japan. Her work stands out for its descriptions of her travels and pilgrimages and is unique in the literature of the period, as well as one of the first in the genre of travel writing.
Keywords: Japanese literature,Văn học Nhật Bản